Can Primary Source Evidence Skills be Improved by using Virtual Field Trip Learning Resources? - Ofianto Ofianto; Erniwati Erniwati; Azmi Fitrisia (AL-ISHLAH: Jurnal Pendidikan, 2023)
The development of historical thinking skills, one must analyze historical event evidence. A thorough, reliable, and trustworthy grasp of history will be created through a variety of historical sources. In order to construct historical narratives, one has to be able to find, recognize, evaluate, interpret, and generalize information from primary source material. In order to fully fulfill this potential, educators must create effective ways. Due to this, the purpose of this study is to (1) explain the value of using original sources to support historical understanding and (2) find ways to use Virtual Field Trip media to help students use primary sources to support their historical learning. A literature review is employed to obtain the answers to the stated research questions. Literature reviews that were pertinent to the issue under study were used to gather research data. The interactive model developed by Miles and Huberman for data analysis included data gathering, data reduction, data display, and conclusion-making. The study's major results point out that (1) using primary source evidence effectively is crucial for developing historical understanding and (2) using virtual field trip media effectively helps students develop higher-order thinking skills, including the ability to use primary sources effectively. According to the conclusions, this article advises teachers to employ learning resources that provide students with hands-on experience.